Teachers’ barriers on the implementation of English online learning during Covid-19 pandemic - Yoyoh Rohayati (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2022)
The COVID-19 pandemic has changed all activities in various fields, including education. Learning that has long been done conventionally, has now been done completely online. This presents various impacts in its implementation. The purpose of this study was to find out the barriers faced by English teachers during online teaching in the pandemic. This research was conducted in one senior high school in Majalengka Regency, with three English teachers as samples. The method used is qualitative research with a case study approach. The research instrument were observation and interviews. The results showed that there were various problems that barriers the online learning process. These barriers are caused by internal and external factors. Where internal factors are problems that come from within the teachers themselves such as (1) teachers have difficulty in building character, (2) lack of knowledge about ICT, (3) teaching styles such as methods and media that teachers use (4) difficulties in building good classrooms. effective, which is caused by learning burnout and lack of interaction, and (5) lack of time. Then the obstacles contained in the external factors are the obstacles experienced by students which can become barriers for teachers in teaching online, including: (1) economic problems and (2) lack of support. It can be concluded that online learning still has various barriers in its implementation so that further research is needed to find a solution, then the learning can be carried out optimally. keywords: teachers' barriers; Covid-19; online learning; English